An economic Manifesto for the oil exporting countries of the Persian Gulf - Hossein Askari; Faranghees Abbas; George Jabbour; Dohee Kwon (PSL Quarterly Review, 2006)
The oil-exporting countries of the Persian Gulf have failed economically and socially. It is time for a radical new approach to managing oil revenues while oil and gas reserves last. We propose an approach to cut the level of oil revenues available to governments to zero while incorporating a formal “Oil Fund for All Generations”. Others have proposed and implemented oil funds but in our proposal the government would (in time) lose all access to oil revenues; by taking easy money away from governments and rulers, the likelihood of waste, corruption and wars will be reduced, and there will be better chance of adopting and implementing rational economic policies to enhance equity across generations.